Impact of spine alignment on the rotator cuff in long-term wheelchair users - Kentar, Yasser; Brunner, Manuela; Bruckner, Thomas; Hug, Andreas; Raiss, Patric; Zeifang, Felix; Loew, Markus; Al Mansour, Haidara; Akbar, Michael (Journal of shoulder and elbow surgery, 2018)
Background - We investigated the impact of poor seated posture on the prevalence of rotator cuff tears (RCTs) among wheelchair-dependent individuals with long-standing paraplegia. - Methods - The study included 319 patients. Lateral radiographs of the spine were collected from a database and analyzed to assess the global spinopelvic alignment (SPA). Magnetic resonance images of both shoulders were obtained to detect the presence of cuff tears. Patients were divided into 2 groups: Group RCT-I included all patients with cuff tears (right, left, or bilateral), whereas group RCT-II consisted exclusively of patients with bilateral cuff tears. We used the classification systems developed by Kendall et al and Roussouly et al to assess the sagittal spine alignment and SPA, respectively. Univariate and multivariate analyses were performed. To fit both models (groups RCT-I and RCT-II) to the data, the 4 spine curves according to Roussouly et al were subdivided into 2 groups: Group SPA-I included both type 1 and type 2, whereas group SPA-II included both type 3 and type 4. - Results - Magnetic resonance images showed a cuff tear in 192 patients (60.19%) (group RCT-I). Among those, 37 patients (11.60%) had tears in both shoulders (group RCT-II). In group RCT-I, 70.31% of the patients had a kyphotic-lordotic posture. The kyphotic-lordotic posture, a longer duration, and a more rostral neurologic level of injury were highly associated with cuff tear prevalence. In group RCT-II, the multivariate analysis showed that only the duration of spinal cord injury was significantly associated with RCTs. - Conclusion - Thoracic hyperkyphosis was associated with a markedly high rate of RCTs. The data from this study may provide support for developing preventive strategies.
Gesehen am 24.10.2019